2019
DOI: 10.1111/iej.13091
|View full text |Cite
|
Sign up to set email alerts
|

NLRP6 suppresses the inflammatory response of human periodontal ligament cells by inhibiting NF‐κB and ERK signal pathways

Abstract: Aim To explore the function and mechanisms of NLRP6 (NOD‐, LRR‐ and pyrin domain‐containing 6) in the inflammatory response of human periodontal ligament cells (HPDLCs). Methodology Tissues associated with apical periodontitis were obtained from three patients who underwent endodontic microsurgery. The expression of NLRP6 in 3 human apical periodontitis tissues and HPDLCs was examined by immunohistochemistry and immunofluorescence, respectively. The expressions of NLRP6, Phospho(p)‐ p65, p65, IκB‐α, p‐ IκB‐α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Among others, bacteria of different taxa were shown to regulate NLPR6 inflammasome formation 27‐29 . In line, the microbial ligands lipopolysaccharide (LPS), MDP, iE‐DAP and Pam3CSK4 have been reported to induce NLPR6 activation in human periodontal ligament cells 19 . Additionally, lipoteichoic acid (LTA), a surface‐associated adhesion amphiphile of Gram‐positive bacteria, induces the formation of NLRP6 inflammasome, and interestingly, in this case NLRP6 activates the non‐canonical pathway involving caspase‐11 in vivo 27 .…”
Section: Nlrp6 Inflammasome Assembly Regulation and Effector Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among others, bacteria of different taxa were shown to regulate NLPR6 inflammasome formation 27‐29 . In line, the microbial ligands lipopolysaccharide (LPS), MDP, iE‐DAP and Pam3CSK4 have been reported to induce NLPR6 activation in human periodontal ligament cells 19 . Additionally, lipoteichoic acid (LTA), a surface‐associated adhesion amphiphile of Gram‐positive bacteria, induces the formation of NLRP6 inflammasome, and interestingly, in this case NLRP6 activates the non‐canonical pathway involving caspase‐11 in vivo 27 .…”
Section: Nlrp6 Inflammasome Assembly Regulation and Effector Functionmentioning
confidence: 99%
“…Chen et al show that alkali‐burn injury induces NLRP3 and NLRP6 inflammasome formation, whereby NLRP3 is activated by NF‐κB, while NLRP6 dampens NF‐κB activity, demonstrating the opposing roles of these two inflammasomes in this context 30 . In human periodontal ligament cells, NLRP6 inhibits NF‐κB and ERK signalling, thereby dampening the release of IL‐6 and TNF‐α 19 . Additionally, NLRP6 inhibits the activation of NF‐κB signalling pathway and p38 mitogen‐activated protein kinase (MAPK) signalling pathway after allogeneic haematopoietic stem cell transplantation‐induced liver damage in mice.…”
Section: Nlrp6 Inflammasome Assembly Regulation and Effector Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4, a transmembrane receptor, is responsible for the activation of a wide range of signal pathways involved in the bactericidal response [26]. Accumulating evidence has shown that the NF-κB signaling pathway serves as a crucial role in the progression of periodontitis [27]. Growing evidence indicated that TLR4-mediated NF-κB signaling plays an important role in the progression of periodontitis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In another study of patients undergoing endodontic microsurgery, analysis of tissues associated with apical periodontitis revealed higher expression of NLRP6. 68 In addition, when NLRP6 was silenced in periodontal ligament cells and then stimulated with E. coli-derived LPS, both NF-κB and ERK signaling were found to be augmented as were secretion of IL-6 and TNF-α. This suggests that NLRP6 suppresses the inflammatory response during periodontitis, which is in line with mouse studies where NLRP6 has been reported to negatively regulate NF-κB and ERK pathways.…”
Section: Nlrp6 In Human Diseasesmentioning
confidence: 98%